PERAN SUPERVISI KEPALA SEKOLAH TERHADAP PELAKSANAAN TUGAS POKOK GURU: PENELITIAN TINDAKAN SEKOLAH - Nirwana Ana Pohan; Yulia Elfrida Yanty Siregar (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2018)
This study aims to reveal the role of supervision of the principal against the implementation of the basic tasks of the teachers in planning, implementing and evaluating the learning process. This research uses Action Research Approach. The results of this research show the results of supervision exercised principals can improve the implementation of the basic tasks of teachers. This also proves that the supervision of the head of school and individual meetings with each teacher to merefleksi learning process had a very important role in enhancing the implementation of the basic tasks of teachers. The implications of this research if a supervision role principals are always carried out, then the learning process in the classroom will give good feedback between teacher and students.. Keyword : Supervision, Head Of School, Research Actions